Pediatric atlanto-occipital dissociation: radiographic findings and clinical outcome - du Plessis, Jean-Pierre; Dix-Peek, Stewart; Hoffman, Eduard Bernard; Wieselthaler, Nicky; Dunn, Robert Neil (Evidence-Based Spine-Care Journal, 2012)
Study design: Retrospective diagnostic feasibility study and clinical review.Objectives: To evaluate the feasibility of making an initial atlanto-occipital dissociation (AOD) diagnosis from four radiological measurements of the craniocervical relationship on lateral cervical spine x-rays and to assess the AOD patients' clinical outcomes relative to their magnetic resonance imaging (MRI) findings.Methods: The Powers ratio, Wackenheim line, basion-dens distance (BDD), and the C1/2:C2/3 interspinous ratio were measured in 58 pediatric controls and ten MRI-confirmed patients with AOD. The ability to identify the required anatomical landmarks and make the measurements was noted and sensitivity and specificity calculated. The correspondence between the clinical presentation and outcomes for patients with AOD and their MRI features was investigated.Results: Clear landmarks for measuring interspinous ratio and Wackenheim line were confirmed by all x-rays. The BDD was measureable in 90% and the Powers ratio could be calculated in only possible in 59%. The interspinous ratio and BDD offered high sensitivities and specificity. Although the Wackenheim line was consistantly measured, it conferred a low sensitivity but reasonable specificity. The Powers ratio offered high specificity with low sensitivity. On MRI, all patients with AOD had apical ligament disruption, with a high rate of interspinous ligamentous injury (8/9); prevertebral swelling (7/9); retroclival hematoma (6/9); and tectorial membrane injury (4/9). The only MRI feature associated with poor outcome was that of altered cord signal. Both patients who died had cord signal changes on T1- and T2-weighted images. The third patient with cord signal change was limited to T2 changes with a normal T1. He had a C5-L3 sensory deficit that resolved. The degree of tectorial membrane injury did not appear to influence outcome.Conclusions: The BDD and interspinous ratio offer the best measures for initial x-ray diagnosis of AOD. This will alert the surgeon to the need for MRI. These patients often have a reduced level of consciousness, thus making clinical evaluation difficult. The MRI findings, although apparently indicative of severe abnormality, did not actually correspond to outcomes except for the presence of T1 cord signal changes that matched with severe neurological impairment and subsequent death.